Conspiratorial Beliefs About COVID-19 Pandemic - Can They Pose a Mental Health Risk? The Relationship Between Conspiracy Thinking and the Symptoms of Anxiety and Depression Among Adult Poles - Dȩbski, Paweł; Boroń, Adrianna; Kapuśniak, Natalia; Dȩbska-Janus, Małgorzata; Piegza, Magdalena; Gorczyca, Piotr (Frontiers in Psychiatry, 2022)
The aim of the study was to describe the relationship between the tendency to believe in false information about the COVID-19 pandemic, tendency to believe in conspiracy theories and the severity of anxiety and depression symptoms among the surveyed Poles. The study was conducted via the Internet in a group of 700 people aged 24.8 ± 6.3 years (mean ± SD). 585 females and 110 males were involved. Scales such as Generic Conspiracist Beliefs Scale (GCBS), Hospital Anxiety and Depression Scale (HADS) and the original questionnaire COVID-19 Conspiratorial Beliefs Scale (COVID-19 CBS) designed to measure the tendency to believe in false information about COVID-19 pandemic were used. A positive correlation was observed between the tendency to believe in false information about the COVID-19 pandemic (COVID-19 CBS) and the tendency to believe in general conspiracy theories (GCBS) (r = 0.768; p < 0.001). Moreover, both COVID-19 CBS and GCBS positively correlated with the severity of anxiety and depression symptoms in the study group. For COVID-19 CBS, the correlation coefficients were 0.087 (p < 0.021) and.108 (p < 0.004) for depressive and anxiety symptoms, respectively, while for GCBS the coefficients were 0.132 (p < 0.001) and 0.147 (p < 0.001). Regression analysis showed that the increased tendency to believe in false beliefs about the COVID-19 pandemic may be associated with an increase in the severity of anxiety (b = 0.04; p = 0.021) and depression (b = 0.06; p < 0.001) symptoms. It can be hypothesized that the tendency to believe in false information regarding the COVID-19 pandemic is positively associated with the tendency to general belief in conspiracy theories. False beliefs about the COVID-19 pandemic may, at least to some extent, influence the development of anxiety and depression symptoms.